Desenvolvimento e caracterização de formulação de uso tópico contendo extrato padronizado de Trichilia catigua para fins cosmético - Lonni, Audrey Alesandra Stinghen Garcia (2012)
In the last few years, several area in Science have been together in order to understand, clarify, detain and revert the aging skin process. It is believed that about 80% of visible signs caused during the aging process are due the ultraviolet radiation and free radicals. The aim of topical administration of antioxidants is to reduce these oxidative damages, therefore promoting the anti-aging action. Studies have been showing that crude extract and isolated substances of Trichilia catigua A. Juss (Meliaceae), popularly known as "Catuaba", showed antioxidant capacity greater than vitamins C and E. With the help of chemometrics, specifically, statistical mixtures design, principal component and hierarchical clustering analysis, and response surfaces provided the highest yields, total polyphenol contents and antioxidant activities of the crude extracts of T. catigua (TCE). The spectra of the chromatographic peaks of quaternary mixtures (water–methanol–acetone–ethanol; 1:1:1:1) indicated the presence of cinchonains, gallic acid derivatives, polyphenols, flavanoids, catechins, and epicatechins. In order to preserve the extract activity in the formulation and in the skin, a W/O/W type multiple emulsion containing TCE in two concentrations: 0,5% (w/w) e 1,0% (w/w) was developed and characterized. Nine formulations were developed with and without extract containing vegetal oils: “andiroba” (Carapa guianensis Aubl.), “buriti” (Mauritia flexuosa L.) and “canola” oil (Brassica napus L.), non-ionic surfactants of low and high HLB, propylene glycol and distillated water. Nanoemulsions were obtained by the phase inversion emulsification method. Formulations were characterized as macroscopic and microscopic aspects, granulometric analysis, pH values, conductivity, and rheology. The characterization tests permitted the selection of the formulations obtained from “canola” oil with and without TCE, in both concentrations. The formulations tested showed Non-Newtonian rheological profile and pseudoplastic behavior with minimal thixotropy. The in vitro release profile of these systems showed that the TCE of emulsion (1.0%) can be released in a controlled manner for a period of 16 h, while the TCE (0.5%) can be released in a controlled manner for a period of 23 h. The percutaneous penetration was evaluated by ex vivo photoacoustic spectroscopy. Was identified the presence of TCE in the epidermis and dermis, more evident with the formulation containing 1.0% TCE. In addition, the histological and histopathological analyzes were investigated in rabbits' ears. The results showed that the formulations are safe under normal or reasonably foreseeable use, its use may be favorable. Finally, the formulation containing canola oil, with and without the TCE (0.5 and 1.0%) were submitted to accelerated stability testing for 90 days. The formulation without ETC proved unstable, with flocculation at low temperatures (-20 °C). The formulation containing 1.0% TCE showed instability with reduced phase separation and the polyphenol content at elevated temperature (40 ° C) after 90 days. The other parameters of evaluation and analysis employed remained stable. The results suggest that the formulations studied are suitable for cosmetic use, however, can’t be exposed to elevated temperature